Shannon Airport - O'Donoghue, Florence, 1895-1967 (1958)
Funeral procession with airport in background.
Photographer: Limerick Leader.
Keywords: Albert, -- Father, O.F.M.Cap., -- 1877-1925; Dominic, -- Father, O.F.M. Cap., -- 1883-1935; Capuchins; Ireland -- History -- 1922-; Photographic prints -- Irish -- 1950-1960